2015
DOI: 10.1016/j.toxicon.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Partial in vitro analysis of toxic and antigenic activities of eleven Peruvian pitviper snake venoms

Abstract: This work used eleven Peruvian snake venoms (Bothrops andianus, Bothrops atrox, Bothrops barnetti, Bothrops castelnaudi, Bothriopsis chloromelas, Bothrocophias microphthalmus, Bothrops neuwiedi, Bothriopsis oligolepis, Bothriopsis peruviana, Bothrops pictus and Bothriopsis taeniata) to perform in vitro experimentation and determine its main characteristics. Hyaluronidase (HYAL), phospholipase A2 (PLA2), snake venom metalloproteinase (SVMP), snake venom serine protease (SVSP) and L-amino acid oxidase (LAAO) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…Estas manifestaciones son el resultado de la acción de los diferentes componentes del veneno (6,7), cuya composición, así como las propiedades biológicas de varias de las especies de Bothrops en el territorio peruano (B. atrox, B. barnetti, B. newidi, B. brazili, B. andianus, etc. ), ya se conocen (8,9). Sin embargo, aún no se han descrito las características ni la composición del veneno de B. roedingeri.…”
unclassified
“…Estas manifestaciones son el resultado de la acción de los diferentes componentes del veneno (6,7), cuya composición, así como las propiedades biológicas de varias de las especies de Bothrops en el territorio peruano (B. atrox, B. barnetti, B. newidi, B. brazili, B. andianus, etc. ), ya se conocen (8,9). Sin embargo, aún no se han descrito las características ni la composición del veneno de B. roedingeri.…”
unclassified
“…The ANOVA results indicate that, despite the observed immunochemical recognition, in clinical practice, different amounts of both antivenoms are required to achieve 50% recognition of a specific venom, confirming the fact that one vial of antivenom does not recognize the same amount of venom for an entire genus, as currently detailed in the inserts of the drugs in question, and furthermore, the need to promote region-specific antivenoms is indisputable since there should be more direct recognition than cross-reactivity. Although greater recognition by the homologous antivenom is expected, it is possible that a venom to which it is not immunized has a higher proportion of some well-recognized proteins and is, therefore, better recognized than the homologous antivenom, which has been described in different studies with Bothrops venom [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CC 50 obtained was 7.86 μg/mL, in the assay using BlV concentration of An assay using endothelial cells incubated with BlV, found that there was no reduction in cell viability (NAUMANN et al, 2011). However, evaluating the cytotoxicity of the cell lines (MGSO3, VERO and HeLa), against venom of Peruvian Bothrops snakes, it was observed that all the venoms were able to reduce viability cell culture in all strains, and Bl-LAAO (L-amino acid oxidase of B. leucurus) is responsible for this cytotoxic activity (GUERRA-DUARTE et al, 2015). NR test also presents some problems in the evaluation of the cytotoxicity, considering that the cytotoxicity is obtained from the decrease in neutral red uptake by cells remaining in the monolayer, disregarding the cells of the supernatant during the washing step.…”
Section: Resultsmentioning
confidence: 99%